Penyebab Kegagalan ASEAN dalam Penyusunan Code of Conduct Sengketa Laut Cina Selatan Selama Periode 2002-2012 - Mia Intentilia, Anak Agung; Dharmiasih, D.A. Wiwik; Nugraha, A. A. Bagus Surya Widya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2017)
This research aims to describe the causes of ASEAN’s failure in making the Code of Conduct for South China Sea dispute during the period of 2002-2012 by using the concept of international organization’s weaknesses and influence of external actor. The above-mentioned dispute involves four ASEAN member states; there are Vietnam, The Philippines, Malaysia, Brunei Darussalam and China, which is not an ASEAN member state. This research perceives that the failure of ASEAN in making Code of Conduct is influenced by internal and external factors. By using qualitative method, the author found that there are three internal factors that challenge ASEAN, namely different national interest among member states, decision-making process based on consensus, and weak dispute settlement mechanism. The external factors are economic relations between ASEAN and China, China’s persuasion efforts to ASEAN, and China’s ability to prevail strategy towards Cambodia. Keywords: South China Sea Dispute, ASEAN, China, Code of Conduct